“They Both had their own Pontius Pilate:” Leonid Dolgopolov and Miron Petrovsky Discussing on Bulgakov and Mayakovsky - Vassili E. Molodiakov (Литературный факт, 2022)
Russian Modernism scholar Leonid Konstantinovich Dolgolopov (1928–1995) in the late 1980s and early 1990s wrote several research articles on life and works of Vladimir Mayakovsky whom he considered one of the greatest Russian poets of the 20th century. Dolgopolov also highly appreciated works of Mikhail Bulgakov; he wrote no papers on him but closely watched other scholars’ research, especially during “Bulgakov’s boom” of the Perestroika years. Dolgopolov carefully read the article about Bulgakov vs. Mayakovsky confrontation by a literary critic and scholar Miron Semenovich Petrovsky (1932–2020) published in influential magazine “Literaturnoe obozreniye” (“Literary Review”) in 1987, June. Petrovsky sent him a copy inscribed “as a sign of agreement and disagreement.” Dolgopolov made detailed marginalia and wrote separated notes on this subject which are published here for the first time (originals in the present author’s collection). Dolgopolov criticised Petrovsky’s approach to the subject which was important to him and briefly outlined his own view. Dolgopolov was interested in the both Bulgakov and Mayakovsky not as much as participants of the literary process, belonging to different camps and polemicizing with each other, but as examples of a collision between the great artist and the political power. Tragic destiny of the Poet / Prophet endowed with a higher mission and dying while completing it was a major subject of Dolgopolov’s late research and literary work.